Representasi Identitas Hibrida melalui Penampilan dan Simbol Perlawanan Santri Transgender di Pesantren Al-Fatah Yogyakarta, Indonesia: The Representation of Hybrid Identity through Performance and Symbol of Transgender Santri Resistance at Al-Fatah Islamic Boarding School of Yogyakarta, Indonesia - Argyo Demartoto (Society, 2020)
This research aims to analyze the process of constructing hybrid identity and symbol as the form of resistance to show off new identity as a transgender santri (student) at Al-Fatah Islamic Boarding School of Yogyakarta, Indonesia. This research was qualitative. The units of analysis and data sources used were santri, religious teachers (Ustaz), the staff of the Regional Office of the Ministry of Religious Affairs in Special Region of Yogyakarta, representatives of religious organizations, and the community around the Al-Fatah Islamic Boarding School of Yogyakarta. Data collection techniques, which were used in this research, consisted of observation, in-depth interviews, and documentation. The triangulation method was used to validate data and then analyzed using the hybrid identity theory of Keri Lyall Smith with an interactive analysis model. The results showed that transgender santri changing their identity through the hybridity process. Mimicry process occurs in 'the third space' of Al-Fatah Islamic Boarding School, as negotiation space where the fight occurs between culture and identity; thus new identity is created without abandoning their genuine identity. Hybridity occurs in the presence of cultural identity resulting from the relationship between Islam culture, in this case, Islamic Boarding School and transgender culture. The presence of the transgender santri is the symbol of resistance against the dominant culture of Islam with various performances or symbols, which are used daily to show off new identity.